A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

3D Models as a Source for Neuroanatomy Education: A Stepwise White Matter Dissection Using 3D Images and Photogrammetry Scans - André S. B. Oliveira; João Vitor A. Fernandes; Vera Louise F. A. Figueiredo; Luciano C. P. C. Leonel; Megan M. J. Bauman; Michael J. Link; Maria Peris-Celda (Brain Topography, 2024)

Fertilization, irrigation and pasture sown to improve herbage production and quality in Nothofagus antarctica silvopastoral systems in southern Patagonia - V. Gargaglione; P. L. Peri; C. Casas; J. P. Mayo; R. Christiansen (Agroforestry Systems, 2024)

Response of forage production to drought in silvopastoral systems in Argentina - Pablo L. Peri; Santiago Toledo; Luis Gándara; Fabio Trinco; Marcos A. Atanasio; Noelia C. Calamari; Edgardo Casaubon; Natalia Martínez; Roxana Ledesma; Federico Gomez; Javier Lara; Lisandro Blanco; et al. (Agroforestry Systems, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Efficient and repeatable in vitro fertilization in rabbits - J.G. Hamze; P. Peris-Frau; B. Galiano-Cogolludo; C. Tomás-Almenar; J. Santiago-Moreno; P. Bermejo-Álvarez (Theriogenology, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

A multi-model approach to explore sustainable food and land use pathways for Argentina - Federico Frank; José Volante; Noelia Calamari; Pablo L. Peri; Baltazar González Chávez; Pablo García Martínez; María J. Mosciaro; Gabriel Martín; Ignacio Benito Amaro; Ignacio Pace Guerrero; Karina Casellas; Melina Zuliani; et al. (Sustainability Science, 2023)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Silvopastoral use of Nothofagus antarctica forests in Patagonia: impact on soil microorganisms - V. Gargaglione; M. Gonzalez Polo; J. Birgi; S. Toledo; P. Peri (Agroforestry Systems, 2022)

Nitrogen but not phosphorus addition affects symbiotic N2 fixation by legumes in natural and semi-natural grasslands located on four continents - Eduardo Vázquez; Per-Marten Schleuss; Elizabeth T. Borer; Miguel N. Bugalho; Maria C. Caldeira; Nico Eisenhauer; Anu Eskelinen; Philip A. Fay; Sylvia Haider; Anke Jentsch; Kevin P. Kirkman; Rebecca L. McCulley; et al. (Plant and Soil, 2022)
Background and aims The amount of nitrogen (N) derived from symbiotic N 2 fixation by legumes in grasslands might be affected by anthropogenic N and phosphorus (P) inputs, but the underlying mechanisms are not known. Methods We evaluated symbiotic N 2 fixation in 17 natural and semi-natural grasslands on four continents that are subjected to the same full-factorial N and P addition experiment, using the 15 N natural abundance method. Results N as well as combined N and P (NP) addition reduced aboveground legume biomass by 65% and 45%, respectively, compared to the control, whereas P addition had no significant impact. Addition of N and/or P had no significant effect on the symbiotic N 2 fixation per unit legume biomass. In consequence, the amount of N fixed annually per grassland area was less than half in the N addition treatments compared to control and P addition, irrespective of whether the dominant legumes were annuals or perennials. Conclusion Our results reveal that N addition mainly impacts symbiotic N 2 fixation via reduced biomass of legumes rather than changes in N 2 fixation per unit legume biomass. The results show that soil N enrichment by anthropogenic activities significantly reduces N 2 fixation in grasslands, and these effects cannot be reversed by additional P amendment.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Gonfienti (Prato, Tuscany, Central Italy), a zooarchaeological snapshot on daily sixth-century Etruscan household life - Chiara Capalbo; Giulia Peri; Paul P. A. Mazza (Archaeological and Anthropological Sciences, 2021)
While Etruscan sites have received considerable attention over the years, scholarly focus has rarely been directed on the faunal remains from the various celebrated archaeological localities. The present is a zooarchaeological analysis of archaeofaunal material from Gonfienti, a renowned Etruscan locality near Prato, in north-central Tuscany. The vast, complex archaeological site includes a large building, called Edifice 1, that was constructed starting from the sixth century BC. Predominant taphonomic signatures, human-induced damage, archaeobiological evidence and mortality patterns obtained from the study of the faunal remains from the building’s main phase of occupation revealed that the householders depended principally on cattle and subordinately on domestic suids for much of their subsistence, although game also formed part of the diet. The zooarchaeological interpretations match up very well with the interpretations of the excavators and archaeologists concerning the function of Edifice 1 and the use of some of its rooms. In addition, the low incidence of in situ weathering, extensive corrosion of cortical bone surfaces possibly by exposure to alkaline solutions and the relatively high frequency of waterfowls in the studied samples suggest that the area hosting Edifice 1 experienced very humid conditions and was surrounded by large wetland expanses at the time of its main Etruscan occupation.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Sensitivity of global soil carbon stocks to combined nutrient enrichment - T. W. Crowther; C. Riggs; E. M. Lind; E. T. Borer; E. W. Seabloom; S. E. Hobbie; J. Wubs; P. B. Adler; J. Firn; L. Gherardi; N. Hagenah; K. S. Hofmockel; et al. (Ecology Letters, 2019)
Soil stores approximately twice as much carbon as the atmosphere and fluctuations in the size of the soil carbon pool directly influence climate conditions. We used the Nutrient Network global change experiment to examine how anthropogenic nutrient enrichment might influence grassland soil carbon storage at a global scale. In isolation, enrichment of nitrogen and phosphorous had minimal impacts on soil carbon storage. However, when these nutrients were added in combination with potassium and micronutrients, soil carbon stocks changed considerably, with an average increase of 0.04 KgCm −2 year −1 (standard deviation 0.18 KgCm −2 year −1 ). These effects did not correlate with changes in primary productivity, suggesting that soil carbon decomposition may have been restricted. Although nutrient enrichment caused soil carbon gains most dry, sandy regions, considerable absolute losses of soil carbon may occur in high‐latitude regions that store the majority of the world's soil carbon. These mechanistic insights into the sensitivity of grassland carbon stocks to nutrient enrichment can facilitate biochemical modelling efforts to project carbon cycling under future climate scenarios.

Thinking in the sustainability of Nothofagus antarctica silvopastoral systems, how differ the responses of seedlings from different provenances to water shortage? - Héctor A. Bahamonde; D. Sánchez-Gómez; J. Gyenge; P. L. Peri; J. M. Cellini; I. Aranda (Agroforestry Systems, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Ten years of seed production and establishment of regeneration measurements in Nothofagus antarctica forests under different crown cover and quality sites, in Southern Patagonia - Héctor A. Bahamonde; M. V. Lencinas; G. Martínez Pastur; L. Monelos; R. Soler; P. L. Peri (Agroforestry Systems, 2018)

Above-ground arthropod community structure and influence of structural-retention management in southern Patagonian scrublands, Argentina - F. J. Sola; P. L. Peri; L. Huertas; G. J. Martínez Pastur; M. V. Lencinas (Journal of Insect Conservation, 2016)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Litterfall and nutrients return in Nothofagus antarctica forests growing in a site quality gradient with different management uses in Southern Patagonia - Héctor A. Bahamonde; P. L. Peri; G. Martínez Pastur; L. Monelos (European Journal of Forest Research, 2015)

Silvopastoral use of Nothofagus antarctica in Southern Patagonian forests, influence over net nitrogen soil mineralization - Héctor A. Bahamonde; P. L. Peri; R. Alvarez; A. Barneix; A. Moretto; G. Martínez Pastur (Agroforestry Systems, 2013)

Estimates of soil carbon concentration in tropical and temperate forest and woodland from available GIS data on three continents - Brenton Ladd; Shawn W. Laffan; Wulf Amelung; Pablo L. Peri; Lucas C. R. Silva; Pina Gervassi; Stephen P. Bonser; Marcelo Navall; Douglas Sheil (Global Ecology and Biogeography, 2013)
Aim Concern about climate change, with the subsequent emergence of carbon markets and policy initiatives such as REDD (reducing carbon emissions by decreasing deforestation and forest degradation), have focused attention on assessing and monitoring terrestrial carbon reserves. Most effort has focused on above‐ground forest biomass. Soil has received less attention despite containing more carbon than above‐ground terrestrial biomass and the atmosphere combined. Our aim was to explore how well soil carbon concentration could be estimated on three continents from existing climate, topography and vegetation‐cover data. Location P eru, B razil, A rgentina, A ustralia, C hina. Methods Soil carbon concentration and leaf area index ( LAI ) as well as GIS ‐derived climate and topography variables for 65 temperate and 43 tropical, forest and woodland ecosystems, were either directly measured or estimated from freely available global datasets. We then used multiple regressions to determine how well soil carbon concentration could be predicted from LAI , climate and topography at a given site. We compared our measurements with top soil carbon estimates from the F ood and A griculture O rganization of the U nited N ations ( FAO ) harmonized world soil map. Results Our empirical model based on estimates of temperature, water availability and plant productivity provided a good estimate of soil carbon concentrations ( R 2 = 0.79). In contrast, the values of topsoil carbon concentrations from the FAO harmonized world soil map correlated poorly with the measured values of soil carbon concentration ( R 2 = 0.0011). Main conclusions The lack of correlation between the measured values of soil carbon and the values from the FAO harmonized world soil map indicate that substantial improvements in the production of soil carbon maps are needed and possible. Our results demonstrate that the inclusion of freely available GIS data offers improved estimates of soil carbon and will allow the creation of more accurate soil carbon maps.

Litter decomposition and nutrients dynamics in Nothofagus antarctica forests under silvopastoral use in Southern Patagonia - Héctor A. Bahamonde; P. L. Peri; R. Alvarez; A. Barneix; A. Moretto; G. Martínez Pastur (Agroforestry Systems, 2012)

Carbon (δ 13 C ) and nitrogen (δ 15 N ) stable isotope composition in plant and soil in S outhern P atagonia's native forests - Pablo L. Peri; Brenton Ladd; David A. Pepper; Stephen P. Bonser; Shawn W. Laffan; Wulf Amelung (Global Change Biology, 2012)
Stable isotope natural abundance measurements integrate across several biogeochemical processes in ecosystem N and C dynamics. Here, we report trends in natural isotope abundance (δ 13 C and δ 15 N in plant and soil) along a climosequence of 33 N othofagus forest stands located within P atagonia, S outhern A rgentina. We measured 28 different abiotic variables (both climatic variables and soil properties) to characterize environmental conditions at each of the 33 sites. Foliar δ 13 C values ranged from −35.4‰ to −27.7‰, and correlated positively with foliar δ 15 N values, ranging from −3.7‰ to 5.2‰. Soil δ 13 C and δ 15 N values reflected the isotopic trends of the foliar tissues and ranged from −29.8‰ to −25.3‰, and −4.8‰ to 6.4‰, respectively, with no significant differences between N othofagus species ( N othofagus pumilio , N othofagus antarctica , N othofagus betuloides ). Principal component analysis and multiple regressions suggested that mainly water availability variables (mean annual precipitation), but not soil properties, explained between 42% and 79% of the variations in foliar and soil δ 13 C and δ 15 N natural abundance, which declined with increased moisture supply. We conclude that a decline in water use efficiency at wetter sites promotes both the depletion of heavy C and N isotopes in soil and plant biomass. Soil δ 13 C values were higher than those of the plant tissues and this difference increased as annual precipitation increased. No such differences were apparent when δ 15 N values in soil and plant were compared, which indicates that climatic differences contributed more to the overall C balance than to the overall N balance in these forest ecosystems.

Do light and alfalfa responses to cloth and slatted shade represent those measured under an agroforestry system? - A. C. Varella; D. J. Moot; K. M. Pollock; P. L. Peri; R. J. Lucas (Agroforestry Systems, 2011)

Dry matter production, morphology and nutritive value of Dactylis glomerata growing under different light regimes - P. L. Peri; R. J. Lucas; D. J. Moot (Agroforestry Systems, 2007)

Validation of a canopy photosynthesis model for cocksfoot pastures grown under different light regimes - P. L. Peri; D. J. Moot; D. L. McNeil (Agroforestry Systems, 2006)